Sex Chromosome Differentiation in the Frog Genus Pseudis Involves Satellite DNA and Chromosome Rearrangements - Gatto, Kaleb P.; Mattos, João V.; Seger, Karin R.; Lourenço, Luciana B. (Frontiers in Genetics, 2018)
The genus Pseudis comprises six frogs of the family Hylidae and only P. tocantins had heteromorphic sex chromosomes detected by classical cytogenetics. In this species, the W chromosome is larger than the Z chromosome and has a large heterochromatic block located between the centromere and the nucleolus organizer region (NOR) in the long arm. This large heterochromatic band is enriched for the PcP190 satellite DNA (satDNA), whereas the Z chromosome bears a smaller C-band adjacent to the centromere in the long arm that is not detected by PcP190 probes. To assess sex chromosome differentiation in the genus Pseudis, we investigated the PcP190 satDNA in P. bolbodactyla, P. cardosoi, P. minuta and P. paradoxa and in one species of Lysapsus, which is the sister genus of Pseudis. PcP190 sequences were isolated,sequenced and the diversity of this class of satDNA was analyzed. To evaluate whether sex-related variations in PcP190 satDNA were present, we used in situ hybridization (for P. bolbodactyla, P. paradoxa, P. cardosoi and P. minuta) and Southern blotting analysis (for all species). We found a low level of sex chromosome heteromorphism in P. bolbodactyla, as a PcP190 cluster was detected in the short arm of one of the homologues of pair 7 exclusively in females. In P. paradoxa, P. minuta and P. cardosoi, PcP190 satDNA is not sex-related, although a cluster of PcP190 sequences could be recognized in the NOR-bearing chromosomes 7 of P. paradoxa and P. minuta and their homologous chromosome 5 of P. cardosoi. By tracking cytogenetic data in a species tree, we may hypothesize that the positioning of the PcP190 site adjacently to the NOR (as observed in the long arm of the W chromosome of P. tocantins) is a derived condition with respect to the location of the PcP190 site apart from the NOR, in the short arm of the NOR-bearing chromosomes 7 (as present in P. bolbodactyla, P. paradoxa and P. minuta) 5 (as present in P. cardosoi) and we discuss about the emergence of PcP190 satDNA as a sex-related trait.